Blended learning intervention on the students’ reading comprehension achievement with different personality traits - Husain, Balqis; Wardiman, Sri Setyarini; Purnawarman, Pupung; Abasa, Zulhasmi (JEES (Journal of English Educators Society), 2024)
Reading is one of fundamental receptive skills that students should master in language acquisition. In fact, many students struggle in reading even they have mastered language acquisition. Non linguistics factor, for instance personality traits affects the student’s reading comprehension process. The research objectives are (1) to identify the effectiveness of blended learning and conventional learning instruction in improving EFL students’ reading comprehension with different personality traits and (2) to explore the differences in students’ impressions regarding integrating blended learning instruction in the EFL class. This research employs a mixed-methods approach. Sixty-six participants of SMA N 1 Pulau Morotai participated in this study as a sample. Research instruments utilize the Eysenck Personality Test (EPI) to determine students' personality types. The TOEFL prediction test is used in the reading comprehension test, and a semi-structural interview is used for the qualitative instrument. In addition, analyzing the data uses Independent T-test and N-Gain Interpretation Test. The descriptive method is utilized to analyze the qualitative data. The finding shows that the average learning outcomes of mix introverted-extroverted students who use blended learning were higher compared to those of mix introverted-extroverted students who use traditional learning models. Unfortunately, even though both had different learning outcomes, these learning models were generally regarded as ineffective due to the N-gain score being less than 40%. As seen from the interview result, blended learning models were regarded as multi-way instructional models that accommodated students' needs despite an inadequate internet connection, enhanced reading comprehension, fostered students' technological proficiency, and provided efficiency and adaptability. HIGHLIGHTS : The average learning outcomes of mixed introverted and extroverted students who use blended learning model were higher than who use traditional learning models Blended learning model was generally regarded as ineffective due to the N gain score less than 40% Blended learning model as a multi-way instructional models that accommodate students’ needs.